Atomic-scale tuning of ultrathin memristors - Ryan Goul; Angelo Marshall; Sierra Seacat; Hartwin Peelaers; Francisco C. Robles Hernandez; Judy Z. Wu (Communications Physics, 2022)
A memristor is an electrical component where its resistance can be preprogrammed and they are expected to play an integral role in future neuromorphic computing devices. Here, the authors report an atomic-scale tuning of ultrathin memristors for which they can obtain greater controllability over the high state resistance and ON/OFF ratio when compared to previous designs.